Immature Oocytes in “Apparent Empty Follicle Syndrome”: A Case Report - Teraporn Vutyavanich; Waraporn Piromlertamorn; Jason Ellis (Case Reports in Medicine)
Empty follicle syndrome (EFS) is a condition in which no oocytes are obtained after an apparently successful ovarian stimulation. Genuine EFS (GEFS) is differentiated from false EFS by an optimal level of human chorionic gonadotropin on the day of oocyte retrieval. Some believe that GEFS does not exist and that it is only a reflection of the margin of error attendant upon the procedure of oocyte aspiration. Others believe that GEFS is caused by dysfunctional folliculogenesis, resulting in early atresia of oocytes. In this report, we present a case of apparent GEFS, in which immature oocytes were identified after filtration of follicular aspirates. Our findings suggest that delayed maturation of oocyte cumulus complexes in response to HCG might be an etiologic mechanism in some cases of GEFS. This creates a situation similar to the aspiration of immature follicles, where germinal vesicle-stage oocytes with dense scanty cumulus cells are often difficult to identify under a dissecting microscope.